Cerámicas de cocina de los siglos V-VII en Cartagena (C/. Orcel – D. Gil) - Láiz Reverte, Mª Dolores; Ruiz Valderas, Elena (Antigüedad y Cristianismo, 1998)
This paper analyses ceramic cooking vessels wich were found during the archaeological dig at the streets Orcel and D. Gil (Cartagena) and which are from the later stages of the sixth and seventh centuries AD. This pottery was certainly produced locally or regionally in workshops, probably from about the middle of the fifth century up until sometime during the seventh century AD. The vessels discovered were entirely those forms used for cooking: varoius types of cooking pots, earthenware bowls and lids.